The Role of Edupreneurship in Gen Z in Shaping Independent and Creative Young Generation - Antri Arta; Muhazzab Alief Faizal; Binti Nur Asiyah; Mashudi (Prodi Ekonomi Syariah Universitas Majalengka, 2023)
This research aims to explore the role of Edupreneurship in shaping an independent and creative Generation Z in the digital era. Edupreneurship is a concept that combines education and entrepreneurship to prepare Generation Z for future challenges. A literature study was conducted by collecting and analyzing related articles, books, and research. The results showed that Edupreneurship provides opportunities for Generation Z to develop the necessary skills, attitudes, and knowledge. The concept encourages entrepreneurship, creative thinking, self-learning, and facing challenges with a positive attitude. This research aims to provide insights for policymakers, educators, and parents in supporting the development of Generation Z. It also provides a basis for policymakers, educators, and parents in supporting the development of Generation Z. In addition, this research also serves as a basis for further research on the implementation of Edupreneurship in Generation Z education.